Three-Dimensional-Printed GelMA-KerMA Composite Patches as an Innovative Platform for Potential Tissue Engineering of Tympanic Membrane Perforations - Bedir, Tuba; Baykara, Dilruba; Yildirim, Ridvan; Koyuncu, Ayse Ceren Calikoglu; Sahin, Ali; Kaya, Elif; Tinaz, Gulgun Bosgelmez; Insel, Mert Akin; Topuzogullari, Murat; Gunduz, Oguzhan; Ustundag, Cem Bulent; Narayan, Roger (MDPI, 2024)
Tympanic membrane (TM) perforations, primarily induced by middle ear infections, the introduction of foreign objects into the ear, and acoustic trauma, lead to hearing abnormalities and ear infections. We describe the design and fabrication of a novel composite patch containing photocrosslinkable gelatin methacryloyl (GelMA) and keratin methacryloyl (KerMA) hydrogels. GelMA-KerMA patches containing conical microneedles in their design were developed using the digital light processing (DLP) 3D printing approach. Following this, the patches were biofunctionalized by applying a coaxial coating with PVA nanoparticles loaded with gentamicin (GEN) and fibroblast growth factor (FGF-2) with the Electrohydrodynamic Atomization (EHDA) method. The developed nanoparticle-coated 3D-printed patches were evaluated in terms of their chemical, morphological, mechanical, swelling, and degradation behavior. In addition, the GEN and FGF-2 release profiles, antimicrobial properties, and biocompatibility of the patches were examined in vitro. The morphological assessment verified the successful fabrication and nanoparticle coating of the 3D-printed GelMA-KerMA patches. The outcomes of antibacterial tests demonstrated that GEN@PVA/GelMA-KerMA patches exhibited substantial antibacterial efficacy against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. Furthermore, cell culture studies revealed that GelMA-KerMA patches were biocompatible with human adipose-derived mesenchymal stem cells (hADMSC) and supported cell attachment and proliferation without any cytotoxicity. These findings indicated that biofunctional 3D-printed GelMA-KerMA patches have the potential to be a promising therapeutic approach for addressing TM perforations.
Keywords: tympanic membrane perforation; gelatin methacryloyl; keratin methacrylolyl; DLP 3D printing; nanoparticle; gentamicin; FGF-2; FIBROBLAST GROWTH-FACTOR; COAXIAL ELECTROSPRAY; DRUG-RELEASE; IN-VITRO; HYDROGELS; NANOPARTICLES; DELIVERY; KERATIN; REPAIR; Chemistry; Science & Technology - Other Topics; Materials Science; Physics